ANALISIS PEMAHAMAN GURU PAI DALAM MENYUSUN PENILAIAN MENGGUNAKAN TEKNIK MULTIPLE CHOICE PADA TINGKAT SMP DI PEKANBARU - Mila Roza (Jurnal Evaluasi Pendidikan, 2022)
In practice PAI teachers are allegedly not understanding the use of multiple choice question models in accordance with the guidelines in preparing questions, because PAI teachers tend to use traditional multiple choice models. This study will reveal what types of multiple choice models have been used by PAI teachers. In addition, we will see the extent of the teacher's understanding in preparing questions based on the guidelines in the guidelines for formulating multiple choice questions. This research uses a qualitative research model with a field research model or field research. In this case the researcher will describe the results of the study in answering the problem formulation, using interview, observation and questionnaire techniques as data collection in the field. The results of this study indicate that PAI teachers are more likely to use the multiple choice question model with the usual model without being varied from one model to another. Meanwhile, the teacher's understanding based on the guidelines for making multiple choice questions is in the good category even though there are several different answers.